2017
DOI: 10.1186/s12904-017-0193-0
|View full text |Cite
|
Sign up to set email alerts
|

To be a trained and supported volunteer in palliative care – a phenomenological study

Abstract: BackgroundIt has been found that including volunteers in palliative care is a positive contribution to seriously ill patients. It is, however, recommended that the volunteers are trained and supported. The aim of this study was to describe a group of trained and supported volunteers’ lived experiences as volunteers in palliative care within the community health care services.MethodsThis study adopted a descriptive phenomenological approach featuring individual interviews with nine volunteers. The interviews we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 21 publications
1
36
2
2
Order By: Relevance
“…They derived great satisfaction from listening and learning from clients, and from assisting clients in their transitions. This relational interaction is a significant motivation for volunteering in the literature [61,63]. Volunteers described the importance of engaging in both small talk and deeply sensitive topics, a finding that was also reported in the ELSA study [41].…”
Section: Volunteer Preparation and Role Satisfactionmentioning
confidence: 66%
See 1 more Smart Citation
“…They derived great satisfaction from listening and learning from clients, and from assisting clients in their transitions. This relational interaction is a significant motivation for volunteering in the literature [61,63]. Volunteers described the importance of engaging in both small talk and deeply sensitive topics, a finding that was also reported in the ELSA study [41].…”
Section: Volunteer Preparation and Role Satisfactionmentioning
confidence: 66%
“…In this study, volunteers indicated a need for further training and a desire to connect with other volunteers. Being part of a supportive community, and feeling well-prepared and mentored in their role is a critical part of volunteer satisfaction [61,62]. In a follow-up study in progress, we are now providing both monthly coaching sessions and ongoing education in various aspects of the volunteer role (e.g., grief, boundaries, healthcare literacy).…”
Section: Volunteer Preparation and Role Satisfactionmentioning
confidence: 99%
“…While not previously explored in the context of breastfeeding, the experiences of peer supporters or volunteers have been explored within other contexts revealing rewards and challenges unique to their situation. A phenomenological study with nine Norwegian volunteers working in palliative care shared how their experience was regarded as positive, meaningful and a privilege [47]. Although these evaluations provide valuable information, it is difficult to draw direct parallels to our study due to the nature of the volunteer input in these differing contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with developed countries, the status quo of "getting old before getting rich" in China makes it likely to face more fiscal pressures in relation to public systems of healthcare, pensions and social protection schemes for older persons [ 1 ]. Previous studies on elderly care services indicated that volunteers can supplement family members’ care and paid staff care [ 4 7 ]. The participation of trained volunteers in old-age care could also be beneficial for the delivery of caring knowledge to relatives and paid housekeepers of community seniors [ 8 ].…”
Section: Introductionmentioning
confidence: 99%